Design of an automated cheese cutting machine prototype (2018)
This work describes each of the parameters for the design of a prototype of an automated machine to make cuts in different types of cheese, in cubic form and slices. Each mechanical and structural component is designed, analyzed and calculated, with the implementation of a compression mechanism with power screw, simulating its operation in the SolidWorks Computer Aided Design (CAD) program, the equipment and accessories that constitute the control system for the automation of the prototype are selected, the programming of the Programmable Logical Control (PLC) in ladder language is carried out. Finally, the operation of the prototype is demonstrated through modeling and simulation with the use of the NI LabVIEW Softmotion module that allows integration with SolidWorks, making the application that involves some components of the prototype and controlling its movements from NI LabVIEW.